Hedonic Quality and Social Norms: a hybrid model of product differentiation - Andrea Mantovani; Ornella Tarola; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
We analyse how strategic competition between a green firm and a brown competitor develops when their products are differentiated along two dimensions: hedonic quality and environmental quality. The former dimension refers to the pure (intrinsic) performance of the good, whereas the latter dimension has a positional content: buying green goods satisfies the consumers' desire to be socially worthy citizens. Product variants thus comply at different levels with "green" social norms. Consumer preferences depend on a combination of hedonic quality and compliance with social norms. Assuming that the high hedonic quality variant complies less with these norms than the low hedonic quality variant, we characterize different equilibrium configurations which appear as a result of both the intensity of such norms and the willingness to pay for the hedonic quality. Afterwards, we discuss the policy implications of our analysis.
Keywords: D62; L13; H13; 330